THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF ALTERGLOBALIZATION PROCESSES - Zvarych, Roman (Journal of European Economy, 2017)
Characterized the civilizational dimensions of global economic development and defined phases of civilization economic development. Evaluated development prospects of neo-liberal model of world economy. Analyzed the theories of the origin and formation of globalization. Formed systemic critic of global processes and its basic critical comments. Researched the process of the Alternative Globalization formation and basic principles of Alterglobalization.